Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21203/rs.3.rs-134052/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual Assessment of Commercial Drivers in the South West Region of Cameroon

Abstract: Background: Driving is a visually intensive task. In Cameroon where the burden of road traffic deaths is high, visual assessment is not universally performed before the issuance of driver’s licenses. This study assesses the visual status of commercial drivers (CDs) in the Southwest Region of Cameroon.Methods: This was a cross-sectional community-based study on CDs in Limbe and Buea. Questionnaires were used to assess socio-demographic parameters, the incidence of road traffic crashes (RTCs), and self-reported … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In high-income countries, specific regulations that are inspired by apparently objective and frequently updated criteria are developed and implemented to guide the assessment of fitness to drive as a holistic and legal concept. 1-3 However, the proportion of drivers in many low-income and middle-income countries (LMICs), including those drivers involved in transportation of the public in large numbers, who are still able to secure a driving licence without ever having their vision assessed might seem shocking 4,5 and reveals challenges in law implementation. Paradoxically, it is observed that these shortcomings do not necessarily translate into a higher proportion of drivers with visual defects and the methods to assess visual function of drivers needs to be revisited.…”
Section: Vision Impairment and Traffic Safety Outcomes In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-income countries, specific regulations that are inspired by apparently objective and frequently updated criteria are developed and implemented to guide the assessment of fitness to drive as a holistic and legal concept. 1-3 However, the proportion of drivers in many low-income and middle-income countries (LMICs), including those drivers involved in transportation of the public in large numbers, who are still able to secure a driving licence without ever having their vision assessed might seem shocking 4,5 and reveals challenges in law implementation. Paradoxically, it is observed that these shortcomings do not necessarily translate into a higher proportion of drivers with visual defects and the methods to assess visual function of drivers needs to be revisited.…”
Section: Vision Impairment and Traffic Safety Outcomes In Lmicsmentioning
confidence: 99%
“…Several studies have attempted to estimate the proportion of drivers with visual defects in all settings and some often attempt to associate the presence of such defects with the risk of occurrence of road traffic crashes. [4][5][6] The Article by Prabhath Piyasena and colleagues in The Lancet Global Health is an interesting overview of the problem, specifically in LMICs, with a focus on the prevalence of visual defects, adherence to visual parameters included in driving licensure requirements, and the possible association with the risk of poor driving outcomes. 7 The systematic review and meta-analysis of 15 7 Assessment of vision as a component of fitness to drive is historically based on perceptual parameters ranging from the most basic-ie, visual acuity, colour vision, and visual fields-to more specific ones such as stereopsis (the ability to appreciate depth), contrast sensitivity, and peripheral vision.…”
Section: Vision Impairment and Traffic Safety Outcomes In Lmicsmentioning
confidence: 99%